Transparency in Biotech Governance: What Informed Citizens Request from Xenotransplantation. - Kögel, Johannes; Marckmann, Georg (NanoEthics, 2026)
Transparency has become a fundamental public value and a linchpin for effective policymaking. Accordingly, emerging biotechnologies, along with their regulatory and implementation frameworks, are increasingly evaluated against this standard. To illustrate this point, we draw on the example of a citizen conference addressing the issue of xenotransplantation. The citizen group expressed conditional support for xenotransplantation, with their approval hinging on specific requirements that can be analyzed through the lens of transparency. Transparency involves at least three key dimensions. First, it required openness and the provision of information to those directly affected by xenotransplantation, such as the transplanted patients. Second, it requires establishing an effective system of checks and balances through regulatory bodies and state authorities. Third, it calls for the disclosure of xenotransplantation research processes to the wider public. Additionally, another vital aspect of transparency – and one that contributes to good policies in the context of citizen participation – is demonstrating how citizens' opinions are genuinely considered and integrated into the policymaking process. Reflecting on the citizen conference as a “showing” of transparency itself, the complete fulfilment of its demands must always appear as lacking, even though such participation formats may facilitate transparency in terms of both visibility and explanation.